Yertle The Turtle and Other Stories - Dr Seuss (Random House Inc, 1986)
This book is a collection of some of Dr Seuss's stories which include Yertle The Turtle, The Big Brag and many more stories.
Keywords: Animals; Juvenile Fiction; Turtles